Influence of working pressure and spray nozzle on the distribution of spray liquid in manual backpack sprayers - Marangoni Junior,Alcides (2019)
ABSTRACT Manual backpack sprayers are widely used in rural properties in Brazil. However, studies that assess their working characteristics, especially spray tip models and working pressure conditions, are scarce. Thus, the aim of this study was to assess how much the working pressure and spray tips influence the distribution quality of phytosanitary spray solutions in manual backpack sprayers. Four spray nozzles (standard flat-fan Magnojet TP11002, turbo flat-fan TeeJet TT11002, hollow-cone TeeJet TXA8002, and disc-core) were assessed in a patternator table at 1, 2, 3, and 4 bar. Analyses of spray distribution profile were performed by symmetry and the coefficient of variation (CV) analysed by the Tukey’s test (p < 0.05). Spray tip models and working pressure influenced in more than 100% the distribution uniformity values of spray solution and in about 50% the useful range of the phytosanitary treatment. Among the models assessed in this study, the turbo flat-fan spray nozzle presents the best set of characteristics to be indicated for manual backpack sprayers aiming at field phytosanitary treatments.